PERKEMBANGAN PARADIGMA PENAFSIRAN KONTEMPORER DI INDONESIA: Studi Kitab Tafsir at-Tanwir - Muhammad Asnajib (UIN Siber Syekh Nurjati Cirebon, 2020)
This article discusses the development of contemporary interpretation (tafsir) paradigm in Indonesia by conducting research on the Tafsir At-Tanwir Book of the Tarjih and Tajdid Muhammadiyah Majlis (councils). The author tried to match the paradigms of contemporary interpretation in Indonesia with the Book of At-Tanwir as an embodiment of the interpretation book that actually appeared in the contemporary era so that the standardized interpretation paradigm was realized. This article begins with an introduction that explains the development of interpretations in details from the beginning when the interpretation emerged to the development of its realm, starting from the interpretation of bi al-ma'thur which was often carried out by previous scholars to the next phase exploring the realm of contextualization which gave rise to the term tafsir bi al-ra’yi. Tafsir bi al-ra’yi arose as a response to the ummat’s problems which have been increasingly developing in each era and have not been discussed in the previous tafsir books. This article also discusses the biography of Muhammadiyah’s founder, KH. Ahmad Dahlan, the establishment process of Muhammadiyah, and the Tarjih and Tajdid Majlis as an initial introduction before entering into the interpretation of At-Tanwir. Furthermore, this article discusses the paradigms of contemporary interpretations, starting from the initial assumptions as a basis to find a way for the interpretation paradigm and methodology to always develop until the direct studies of the Tafsir At-Tanwir Book which was initiated by Muhammadiyah.